Residents' perceptions of tourism and their implications for policy development: evidence from rural Poland. Issue 1 (1st January 2016) - Kosmaczewska, Joanna; Thomas, Rhodri; Dias, Francisco
Abstract: Academics and policy-makers have long been interested in understanding the interplay of factors that influence resident perceptions of local tourism development. This article reports the results of a study that is both methodologically and contextually novel. It uses the chi-square automatic interaction detection method (CHAID), which is usually associated with other fields, most notably consumer marketing, to examine residents' perceptions of tourism development in rural Poland. It contributes to the literature by revealing the need to segment residents appropriately and highlights which constituencies in rural communities are most likely to be positively (and negatively) disposed toward tourism. This creates opportunities for more nuanced policy interventions.